Development of the Physiotherapy Therapeutic Relationship Measure. (3rd September 2022) - McCabe, Erin; Miciak, Maxi; Roduta Roberts, Mary; Sun, Haowei (Linda); Kleiner, Michelle J.; Holt, Christopher J.; Gross, Douglas P.
Abstract: Purpose: To describe the development of a new measure of therapeutic relationship for use in physiotherapy – the Physiotherapy Therapeutic RElationship Measure (P-TREM). Methods: We adopted the methodology of Devellis in Scale Development: Theory and Applications for constructing the P-TREM. We developed a measurement framework based on Miciak's Physiotherapy Therapeutic Relationship Conceptual Framework. We generated a pool of items by extracting items from existing measures and writing new items. These were reviewed by a panel of experts and then formatted into a draft measurement instrument. The draft instrument was tested for relevancy and comprehensibility in potential respondents from our target populations using cognitive interview techniques. Finally, we pilot tested the full administration of the P-TREM. Results and conclusions: We systematically constructed the P-TREM with 49 items in 3 subscales. Our rigorous instrument development approach ensures its content validity, which was also demonstrated in the cognitive interviews and pilot testing. The quality of the items and construct validity will be assessed in a subsequent validation study.